Peripheral neuropathy among patients with type II diabetes attending a teaching hospital Chitwan - KC, Nirmala; Kumari Subba, Hem; Khatiwada, Saurav (Journal of Chitwan Medical College, 2026)
Introduction: Diabetes is a growing global health concern with significant morbidity and mortality. Diabetic peripheral nephropathy (DPN) is a common debilitating microvascular complication of diabetes mellitus. This study aimed to find peripheral neuropathy among patients with type II diabetes mellitus. Method: A cross-sectional descriptive study was conducted among patients with type II diabetes mellitus attending endocrine medicine outpatient department of Chitwan Medical College Teaching Hospital, Nepal, during 24 Sep to 22 Oct 2023 Ethical approval was obtained. Data were collected from consecutive eligible patients using a structured interview schedule for socio-demographic and disease-related information, personal habits, and the Michigan Neuropathy Screening Instrument to assess DPN. Data were analysed using IBM SPSS v.23 with descriptive statistics and inferential statistics (chi-square test) to measure associations, and p<0.05 considered statistically significant. Result: Out of 182 patients, females 95(52.2%), 21.4% of patients had mild peripheral neuropathy, none of the patients had moderate and severe peripheral neuropathy. There was significant association between peripheral neuropathy with education (p=0.037), intake of anti-diabetes medicine (p=0.027) and smoking habit (p=0.027) of patients. Conclusion: Nearly one fourth of type II diabetes mellitus patients have peripheral neuropathy. Hence regular screening is necessary to all diabetes patient to prevent the progression of peripheral neuropathy.